‘Beperkte afschrikkingsmacht’ van de Republiek Zuid-Afrika - Kubiak, Krzysztof (Department of Dutch and South African Studies, Faculty of English, 2011)
In the seventies South Africa became a nuclear power. This paper examines the circumstances of and reasons for developing national nuclear capacities. The author presents the political and strategic situation of South Africa and the new threats and challenges which appeared after the collapse of Portuguese colonies in Africa and the arrival of the first Cuban units in Angola. In this context the South African authorities considered the development of nuclear weapons as a fundamental factor in creating a balance of power, and also as an important political tool. It must be emphasised that South Africa saw its own nuclear capacity as an instrument of policy, rather than a classical type weapon to be used on the battlefield. At the end of the apartheid era the South African nuclear bombs were deactivated and dismantled. The country also stopped construction of ballistic missiles. At present the Republic of South Africa is ‘free’ of nuclear weapons.
Keywords: international security; Republic of South Africa; weapon of mass destruction; nuclear weapon; proliferation of weapon of mass destruction; nuclear disarmament